2009
DOI: 10.1523/jneurosci.0796-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Association Fiber Tracts Impairs Recognition of the Facial Expression of Emotion

Abstract: An array of cortical and subcortical structures have been implicated in the recognition of emotion from facial expressions. It remains unknown how these regions communicate as parts of a system to achieve recognition, but white matter tracts are likely critical to this process. We hypothesized that (1) damage to white matter tracts would be associated with recognition impairment and (2) the degree of disconnection of association fiber tracts [inferior longitudinal fasciculus (ILF) and/or inferior fronto-occipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
186
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 85 publications
13
186
0
2
Order By: Relevance
“…In a large group of patients with focal brain lesions (n ϭ 103), damage associated with the right inferior fronto-occipital fasciculus significantly predicted overall facial emotion recognition impairment with specific deficits recognizing sadness, anger, and fear. 38 The inability to properly identify and recognize facial emotions is a wellknown impairment in ASD. 39 Moreover, previously published DTI studies lend support to abnormalities of the inferior fronto-occipital fasciculus in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In a large group of patients with focal brain lesions (n ϭ 103), damage associated with the right inferior fronto-occipital fasciculus significantly predicted overall facial emotion recognition impairment with specific deficits recognizing sadness, anger, and fear. 38 The inability to properly identify and recognize facial emotions is a wellknown impairment in ASD. 39 Moreover, previously published DTI studies lend support to abnormalities of the inferior fronto-occipital fasciculus in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Its function is still being investigated but evidence suggests a supportive role in processing attentional, semantic language and visual information (Sarubbo, De Benedictis, Maldonado, Basso, & Duffau, 2013). Lesion studies have shown that damage to the IFO impairs the recognition of facial affect (Philippi, Mehta, Grabowski, Adolphs, & Rudrauf, 2009). Given that depression has been associated with a negative attentional processing bias (Jacobs, Reinecke, Gollan, & Kane, 2008;Vilgis, Silk, & Vance, 2015), it is likely that alterations in white matter microstructure of the IFO relate to alterations in facial affect processing.…”
Section: Discussionmentioning
confidence: 99%
“…These tracts connect frontal with occipital and posterior parietal and temporal lobes. They integrate auditory and visual association cortices and may have a role in the spatial awareness and neglect, as well as emotion recognition and expression [47] . The fronto-occipital WM abnormality could be related to altered body perception shown in AN.…”
Section: Summary Of Findingsmentioning
confidence: 99%